ANALISIS DAMPAK PENGGUNAAN GAWAI TERHADAP KARAKTER PROFIL PELAJAR PANCASILA KELAS V SD PENERUS BANGSA KOTA TANGERANG - Nabila Irmawati; Enawar; Arry Patriasurya Azhar3 (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Analysis of the Impact of Gadget Use on the Character Profile of Pancasila Students of Grade V of Penerus Bangsa Elementary School, Tangerang City.This research is motivated by the issue of student character being affected by excessive gadget use. In today's digital era, gadgets have become a part of daily life, including among elementary school students. However, uncontrolled gadget use can have negative impacts on students’ character, especially those that reflect the dimensions of the Pancasila Student Profile. The purpose of this research is to describe both the positive and negative impacts of gadget use on the six character dimensions of the Pancasila Student Profile, which include: faith in God Almighty and noble character, independence, critical thinking, creativity, cooperation, and global diversity among fifth-grade students at SD Penerus Bangsa, Tangerang City. This study uses a qualitative descriptive method. The research was conducted at SD Penerus Bangsa, Tangerang City, from October 2024 to March 2025. The research subjects were fifth-grade students, while the informants included fifth-grade teachers, students, and parents. Data collection techniques included observation, interviews, documentation, and questionnaires. The data analysis techniques involved data collection, data reduction, data presentation, and drawing conclusions. Data validity was ensured through technique and source triangulation. The results of the study show that gadget use has various effects on the character of students based on the Pancasila Student Profile. The positive impacts include increased critical thinking skills, creativity, and student independence in seeking information. Meanwhile, the negative impacts include a decline in religious attitudes, reduced social interaction, and weakened cooperation. Therefore, guidance and supervision from both parents and teachers are necessary to ensure that gadget use contributes positively to character development in accordance with the values of the Pancasila Student Profile.